2005
DOI: 10.1152/ajpregu.00104.2005
|View full text |Cite
|
Sign up to set email alerts
|

Localized vs. systemic inflammation in guinea pigs: a role for prostaglandins at distinct points of the fever induction pathways?

Abstract: In guinea pigs, dose-dependent febrile responses were induced by injection of a high (100 g/kg) or a low (10 g/kg) dose of bacterial lipopolysaccharide (LPS) into artificial subcutaneously implanted Teflon chambers. Both LPS doses further induced a pronounced formation of prostaglandin E 2 (PGE2) at the site of localized subcutaneous inflammation. Administration of diclofenac, a nonselective cyclooxygenase (COX) inhibitor, at different doses (5, 50, 500, or 5,000 g/kg) attenuated or abrogated LPS-induced fever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 39 publications
(56 reference statements)
3
40
0
1
Order By: Relevance
“…Recent studies showed that, along the potential neural pathways of neuroimmune communication, nonendothelial IL-1R1 and Cox-2 may play important roles. Thus, Rummel et al (2005) showed that the production of prostaglandin E 2 at the site of local inflammation is critical for the induction of fever, and Samad et al (2001) showed spinal neuronal expression of Cox-2 and IL-1R1 relay signals from localized peripheral inflammation to the brain via ascending sensory nerve tracts. Therefore, CNS activation via these neural pathways would still depend on the expression of Cox-2 and IL-1R1, although endothelial expression of IL-1R1 and Cox-2 may not be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that, along the potential neural pathways of neuroimmune communication, nonendothelial IL-1R1 and Cox-2 may play important roles. Thus, Rummel et al (2005) showed that the production of prostaglandin E 2 at the site of local inflammation is critical for the induction of fever, and Samad et al (2001) showed spinal neuronal expression of Cox-2 and IL-1R1 relay signals from localized peripheral inflammation to the brain via ascending sensory nerve tracts. Therefore, CNS activation via these neural pathways would still depend on the expression of Cox-2 and IL-1R1, although endothelial expression of IL-1R1 and Cox-2 may not be involved.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that localised formation of PGE2 at sites of inflammation contribute to fever generation by activating cold-sensitive cutaneous nerves, which, in turn, transmit fever signals to parts of the brain responsible for fever generation [28]. The transmission of fever signals via the vagus nerve follows a more complex pathway.…”
Section: The Neural Pathwaymentioning
confidence: 99%
“…Better models have been developed of so-called restricted local inflammation that do not induce brain COX-2 and have low to undetectable circulating cytokines. In these studies the fever response could be attenuated by very low doses of locally administrated diclofenac (Rummel et al, 2005) and could be shown to be dependent on the presence of TLR4, IL-1R1, IL-6 and COX-2 (Zhang et al, 2008).…”
Section: Afferent Neuronal Pathwaysmentioning
confidence: 92%
“…While largely neglected at that time this study gained more attention when the antipyretic effect of local anesthetics blocking C-fiber-signaling was verified by Roth's group (Ross et al, 2000;Roth and De Souza, 2001). Several models for local inflammation have been used, including subcutaneous turpentine (Cooper and Rothwell, 1991;Fantuzzi et al, 1997;Horai et al, 1998;Kozak et al, 1998;Laflamme and Rivest, 1999;Leon et al, 1996), carrageenaninduced paw edema (Guay et al, 2004;Ibuki et al, 2003;Oka et al, 2007;Posadas et al, 2004;Prajapati et al, 2014), or immune stimuli administrated in artificial subcutaneous chambers (Cartmell et al, 2000;Miller et al, 1997;Rummel et al, 2005;Rummel et al, 2011;Zhang et al, 2008). However, most studies used local inflammation-models primarily to demonstrate an endotoxin-free cytokine-induced sickness syndrome (Horai et al, 1998;Kozak et al, 1998;Leon et al, 1996;Miller et al, 1997;Rivest et al, 2000) and not to investigate the role played by the afferent neurons.…”
Section: Afferent Neuronal Pathwaysmentioning
confidence: 99%